2017
DOI: 10.3390/rs9121290
|View full text |Cite
|
Sign up to set email alerts
|

Saliency Map Generation for SAR Images with Bayes Theory and Heterogeneous Clutter Model

Abstract: Saliency map generation in synthetic aperture radar (SAR) imagery has become a promising research area, since it has a close relationship with quick potential target identification, rescue services, etc. Due to the multiplicative speckle noise and complex backscattering in SAR imagery, producing satisfying results is still challenging. This paper proposes a new saliency map generation approach for SAR imagery using Bayes theory and a heterogeneous clutter model, i.e., the G 0 model. With Bayes theory, the rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…λ is the regularization parameter in (8) and soft thresholding in (9), which controls the reconstructed precision and the sparsity of the estimated scene.…”
Section: F Soft Thresholding Attention Block (Sta)mentioning
confidence: 99%
See 1 more Smart Citation
“…λ is the regularization parameter in (8) and soft thresholding in (9), which controls the reconstructed precision and the sparsity of the estimated scene.…”
Section: F Soft Thresholding Attention Block (Sta)mentioning
confidence: 99%
“…As one of the important applications of remote sensing, ship detection in synthetic aperture radar images has attracted significant attention in recent years [1]- [8]. Ship detection is also applicable to tactical deployments and ocean defense early warning systems.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al developed a saliency model to extract rivers in highresolution SAR imageries [27]. Xiang et al presented a saliency map generation algorithm, which is shown to be robust to SAR speckle noise and can achieve high accuracy [28]. These applications demonstrate the feasibility and potential of applying saliency to practical SAR object detection.…”
Section: Introductionmentioning
confidence: 99%
“…SAR images are widely used across numerous fields. For example, military applications include target detection, precision guidance, and impact assessment, and the civil areas include terrain mapping, crop growth assessment, and environmental and disaster monitoring [2,3,4,5,6,7,8,9,10]. With the development of radar satellite technology, the collected radar image data shows blowout growth.…”
Section: Introductionmentioning
confidence: 99%